Quality of life in adolescents with heavy menstrual bleeding: Validation of the Adolescent Menstrual Bleeding Questionnaire (aMBQ). Issue 7 (8th November 2021) - Pike, Meghan; Chopek, Ashley; Young, Nancy L.; Usuba, Koyo; Belletrutti, Mark J.; McLaughlin, Robyn; Van Eyk, Nancy; Bouchard, Amanda; Matteson, Kristen; Price, Victoria E.
Abstract: Background/Objectives: Heavy menstrual bleeding (HMB) affects 34% to 37% of adolescent girls. The Menstrual Bleeding Questionnaire (MBQ) is a validated measure of menstrual bleeding–specific health‐related quality of life (HRQoL) for women aged ≥18 years. No similar measure existed for adolescents with HMB. Patients/Methods: HMB was defined by the Pictorial Bleeding Assessment Chart (PBAC) score ≥100. In Phase 1, a focus group of adolescents with HMB adapted the MBQ, to generate the Adolescent MBQ (aMBQ). In phase 2, participants with and without HMB were recruited from clinics and self‐referral. Each participant completed 3 questionnaires (aMBQ, Pediatric Quality of Life module [PedsQL] ©, PBAC) at two time points. Validity of the aMBQ was assessed by Pearson's correlation with the PedsQL © . Reliability was calculated using intra‐class correlation (ICC) in those without HMB. The receiver operating characteristic curve assessed the aMBQ's ability to identify those with HMB. Results: Phase 1 included five girls with a mean age of 17.1 (13‐18) years. The aMBQ was adapted from the MBQ by substituting four words/phrases that altered 8 of the 20 questions and by adding 1 new question. The 21‐item aMBQ has a score range of 0 to 77 (77 = worst HRQoL). Phase 2 included 52 participants: 20 with and 32 without HMB, with a mean age of 14.8 (11‐17) years. The validity of the aMBQ was confirmed by a moderate correlation with PedsQL © (r = −0.63; P < .001). Test‐retest reliability was substantial (ICC = 0.73; P = .04). An aMBQ score of >30 identified those with HMB with excellent discrimination (area under the curve = 0.82; sensitivity, 70.0%; specificity, 84.4%). Conclusions: The aMBQ is a valid and reliable tool to assess HRQoL in adolescents with HMB.